1994
DOI: 10.14742/ajet.2080
|View full text |Cite
|
Sign up to set email alerts
|

A process approach to the transfer of training

Abstract: In the previous article [Foxon, 1993] the author presented two models of transfer. The first, based on force field analysis, highlights the inhibiting and facilitating factors that impact transfer. In particular, intention to transfer and the perceived level of supervisor support were discussed. The second model conceptualises transfer in terms of a five stage process (ranging from initiation to unconscious maintenance) rather than as an outcome or product of training. In this article three strategies to facil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 19 publications
0
31
0
1
Order By: Relevance
“…Building upon Laker' s work, Powell (2009) examined the effects of employees' perceptions of transfer intentions, general self-efficacy (GSE), and supervisor support to identify better the conditions for actual transfer based on Laker' s temporal dimension concept. Laker' s (1990a) multidimensional perspective has received some support (Foxon, 1993(Foxon, , 1997Yamnill & McLean, 2001). As with the contention of the present discussion concerning the differences between hard and soft skills, the Yelon and Ford (1999) perspective of open versus closed tasks and degree of supervision refers to the specific content of the training rather than to different dimensions of the underlying nature of transfer of training itself.…”
Section: Differences Between Hard-and Soft-skills Trainingmentioning
confidence: 86%
See 1 more Smart Citation
“…Building upon Laker' s work, Powell (2009) examined the effects of employees' perceptions of transfer intentions, general self-efficacy (GSE), and supervisor support to identify better the conditions for actual transfer based on Laker' s temporal dimension concept. Laker' s (1990a) multidimensional perspective has received some support (Foxon, 1993(Foxon, , 1997Yamnill & McLean, 2001). As with the contention of the present discussion concerning the differences between hard and soft skills, the Yelon and Ford (1999) perspective of open versus closed tasks and degree of supervision refers to the specific content of the training rather than to different dimensions of the underlying nature of transfer of training itself.…”
Section: Differences Between Hard-and Soft-skills Trainingmentioning
confidence: 86%
“…and soft skills (intrapersonal skills such as one' s ability to manage oneself as well as interpersonal skills such as how one handles one' s interactions with others.) Anecdotal evidence has routinely shown that soft-skills training is significantly less likely to transfer to the job than hard-skills training (Foxon, 1993;Georgenson, 1982;Kupritz, 2002). Most studies of training transfer identify the specific skills being trained, but often do not specifically consider the significance of whether they are either hard or soft skills.…”
Section: Introductionmentioning
confidence: 99%
“…Motivation can create very powerful learning constructs that often make up for the lack of instructional rigor or positive learning climate. Conversely, well designed training with appropriate follow-up and feedback may not make up for a lack of motivation to learn (Foxon, 1993). While not the only key, motivation is a central component in the puzzle of improving transfer effectiveness.…”
Section: Motivationmentioning
confidence: 99%
“…Some research suggests that work environment accounts for 42% of the identified inhibiting factors in the transfer process (Foxon, 1993). Within the context of organization climate, we will discuss both job support and organizational support factors since they are often found in closely linked in both research and the minds of employees.…”
Section: Situational Characteristics That Influence Training Transfermentioning
confidence: 99%
“…While it is obviously most important that learners actively transfer what they have learned in training to their work, research has shown that the intention to transfer has a strong relationship to the transfer process. In other words, as Foxon (1993) asserts, if trainees leave training without transfer intention then they will be unlikely to perform behaviors learned in training on the job later on. To support this assertion, Foxon cites a study by Huczynski and Lewis (1980) of the outcomes of intention to transfer, where the researchers questioned course attendees four months after the training and found that transfer initiation was more likely to occur among trainees with a higher level of intention to transfer.…”
Section: Re-evaluation Of Experiencementioning
confidence: 99%